The role of sewage sludge biochar in methylmercury formation and accumulation in rice. (March 2019) - Zhang, Jin; Wu, Shengchun; Xu, Zhentao; Wang, Minyan; Man, Yu Bon; Christie, Peter; Liang, Peng; Shan, Shengdao; Wong, Ming Hung
Abstract: Methylmercury (MeHg) can accumulate in rice and this has been demonstrated to be an important human MeHg exposure pathway. How to reduce MeHg concentrations in rice grains has therefore become a very important public health issue. Previous studies have investigated the role of plant biochars on Hg bioavailability in soils but knowledge of the influence of sewage sludge biochars (SSB) on MeHg formation and bioaccumulation in different soils is lacking. In the present study, SSB was applied to two Hg-contaminated soils, one acid and the other calcareous, in an attempt to stabilize MeHg in the soil and further mitigate MeHg accumulation in rice grains. The results indicate that the presence of SSB may promote Hg methylation in an acid soil. Moreover, MeHg concentrations increased gradually during rice growth, perhaps due to the release of root exudates. SSB can inhibit both MeHg and total Hg (THg) accumulation in different rice tissues. Both MeHg and THg decreased in the rice grains by up to 73.4 and 81.9%, respectively. However, the inhibitory effect was less pronounced in a calcareous soil. This study further demonstrates that biochar application can inhibit MeHg accumulation in soils despite the promotion of MeHg formation in soil by SSB application. However, an effect of biochar on MeHg accumulation was observed only in the acid soil. These results are useful in managing applications of biochars to Hg-contaminated paddy fields. Highlights: SSB application reduced MeHg accumulation in rice in acid soil. SSB application resulted in the increase of MeHg concentration in acid soil. MeHg accumulation in rice root decreased during rice growth period. Release of rice root exudates lowered soil pH and further promoted MeHg formation.